2007
DOI: 10.1118/1.2437282
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Gamma Knife® helmet factors using MOSFETs

Abstract: The relative dose rate for the different Gamma Knife helmets (4, 8, 14, and 18 mm) is characterized by their respective helmet factors. Since the plateau of the dose profile for the 4 mm helmet is at most 1 mm wide, detector choices are limited. Traditionally helmet factors have been measured using 1 x 1 x 1 mm3 thermoluminescent dosimeters (TLDs). However, these are time-consuming, cumbersome measurements. This article investigates the use of metal-oxide-semiconductor field effect transistors (MOSFETs) (activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…( 20 ) MOSFET systems have recently been investigated for use in electron beam dosimetry, ( 21 23 ) as well. In this study, the application of the mobileMOSFET dosimeter system (Best Medical Canada, Ottawa, ON) to small field electron dosimetry is characterized and compared to conventional film and ionization chamber systems for determining required critical parameters for patient treatments.…”
Section: Introductionmentioning
confidence: 99%
“…( 20 ) MOSFET systems have recently been investigated for use in electron beam dosimetry, ( 21 23 ) as well. In this study, the application of the mobileMOSFET dosimeter system (Best Medical Canada, Ottawa, ON) to small field electron dosimetry is characterized and compared to conventional film and ionization chamber systems for determining required critical parameters for patient treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, there is no standard dosimeter for small fields because no detector has all the aforementioned properties. Commonly used dosimeters in small fields are ionization chambers,[ 23 24 ] films,[ 25 ] thermoluminescent dosimeters (TLDs),[ 26 ] polymer gels,[ 27 ] metal oxide semiconductor field effect transistors (MOSFETs),[ 28 ] diamond detectors,[ 29 ] silicon diodes,[ 30 ] alanine dosimeters,[ 31 ] and Monte Carlo (MC) simulations,[ 32 33 ] among others. The advantages and disadvantages of these detectors will be discussed next.…”
Section: Various Dosimeters Used In Small-field Dosimetrymentioning
confidence: 99%
“…Therefore diodes and films are not employed. Using thermoluminescent diodes (TLDs) could offer an alternative, but several studies have reported their fragility and the need for lengthy calibration and tedious reading [6]. The sensitive surface of a MOSFET is so small that it can be considered as a point measure.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitive surface of a MOSFET is so small that it can be considered as a point measure. Therefore, MOSFETs could be suitable for in-vivo assessment of radiosurgery microbeams [7,6,8]. In the literature their use has been described extensively for such in vivo procedures as: in vivo dosimetry for external radiotherapy [9,10,11], dose verification in intensity modulated radiotherapy (IMRT) [12,13,14], measurements in head and neck Tomotherapy [15], skin dose measurement [16], entry dosimetry [17], implantable detectors for in-situ testing during radiation therapy treatment [18], dose verification of permanent low-dose-rate implants [19] and as a dosimeter for imaging in radiological procedures [20].…”
Section: Introductionmentioning
confidence: 99%